A ilusão da formalidade: a consolidação de padrões e suas contradições em prédios habitacionais no Aglomerado da Serra, Belo Horizonte - Debora Andrade Gomes Moura (2017)
The purpose of this thesis is to present a perspective on the move of inhabitants from a informal context, with space practices to which they were accustomed, to spaces conceived by planners. The object of analysis of this work is the impact in the daily life of the Aglomerado da Serra residents move to the buildings constructed by the Vila Viva Program within the favela. It is considered as well the impact on residents from outside the Aglomerado, who bought the apartments after the construction. The research seeks to understand how the production of space was affected; it is an action research, a method used as a tool for surveying the difficulties encountered, conflicts and ways of acting in collective use spaces. The actions included interviews with dynamics, collective conversations and an experiment with interfaces. Participants discourses often reflect positive assessments of interventions and an ideal of widespread formality in society, although it does not manifest itself effectively in everyday collective spaces of buildings. The critique developed throughout the thesis raises a necessary reflection, which clarifies existing contradictions regarding the consolidation of patterns of consumption and desire that invade the residents imaginary. The ultimate goal is to expand the possibilities of propositional action in contexts of transition to formal environments, having as horizon issues such as identity (class), collectivity and historical consciousness about production of space.